School Leadership Transformation: Improving Teacher Performance through Strategic Decision-Making - Nisaul Fadhilah; Muhammad Wildan Shohib; Pandang Margatama; Ahamad Nubail (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This study explores the principal's decision-making practices at SMP Muhammadiyah 5 Kandangan, focusing on the stages of identification, development and decision selection. The findings show that through a structured process involving the participation of all relevant parties, school principals can make adaptive and responsive decisions to environmental changes. Theoretical implications highlight the importance of integrating school leadership theory with effective decision-making practices. This study offers valuable guidance for educational practitioners in developing results-oriented leadership strategies. As a result, this research shows the need for further research in developing new models for more effective principal decision-making and an emphasis on ethical aspects in decision-making. Thus, improving school principals' decision-making practices is expected to impact educational progress in junior high schools positively.